Does Sport Celebrity Advocacy Work? Testing the Potential for Endorsements to Backfire. Issue 3 (27th May 2017) - Schartel Dunn, Stephanie G.; Nisbett, Gwendelyn S.
ABSTRACT: Fandom and psychological reactance theory, a framework for understanding reactions to messages perceived to limit an individual's freedom to choose freely, are used to examine the influence of sports celebrities. An experiment was conducted ( n = 283) to examine the impact of source similarity and controlling language use on reactance levels and message evaluations. Findings suggest that sources perceived to be similar generated less reactance than dissimilar sources. Similar source messages were also linked to greater potential for information-seeking behavior. High- versus low-controlling language use was examined in conjunction with similarity; low-controlling language was found to generate the least reactance regardless of source similarity. Implications for the use of celebrity advocacy in marketing and public relations are discussed.